The mass market for history paintings in seventeenth-century Amsterdam production, distribution, and consumption - Jager, Angela 1984- (Amsterdam studies in the Dutch Golden Age, 2020)
Millions of paintings were produced in the Dutch Republic. The works that we know and see in museums today constitute only the tip of the iceberg - the top-quality part. But what else was painted? This book explores the low-quality end of the seventeenth-century art market and outlines the significance of that production in the genre of history paintings, which in traditional art historical studies, is usually linked to high prices, famous painters, and elite buyers. Angela Jager analyses the producers, suppliers, and consumers active in this segment to gain insight into this enormous market for cheap history paintings. What did the supply consist of in terms of quantity, quality, price, and subject? Who produced all these works and which production methods did these painters employ? Who distributed these paintings, to whom, and which strategies were used to market them? Who bought these paintings, and why?